Universality in Quantum Computation - Deutsch, D; Barenco, A; Ekert, A (1995)
We show that in quantum computation almost every gate that operates on two or more bits is a universal gate. We discuss various physical considerations bearing on the proper definition of universality for computational components such as logic gates.